Humana vox: as dimensões manuscritas, performáticas e poéticas da monodia vocal - Abreu, Tiago Éric de (2020)
This is a study of vocal writing forms and voice performance in notated monodic vocal compositions of the ritualistic and religious fields, from Antiquity to the Middle Ages. It is a reflection upon the joint of melody and musical text, that provides elements for the interpretation of Medieval music, and can also bestirs creation through performance and composition. This work puts forth interpretations of Medieval manuscripts of Biblitohèque nationale de France (GALLICA, 2020), History tractates and contemporary studies of Greek and Latin monodies. It is proposed an approach of music and poetical conceptions gathered, searching in the origins of musical scripture elements to widen the conceptions of vocal performance, and asking questions about the ways melodies and sang texts interact semantically. This work intends to destabilize theoretical territories and stick out the possibility of phenomenological discovery of the act of chanting, based on ancient motives or “archaic” forms of conceiving chant. This work dialogues with medievalist Leo Treitler’s (2007) musicological approaches, so as to problematize the dichotomy between oral traditions and music scriptural practices, beginning with a reflection upon the musical notation systems which were developed since Antiquity to the end of High Middle Ages (10th century). The Greek registers of written music are inquired firstly in this study, for they allow us to observe the conjunction of three musical phenomena: performance, aural composition and musical scripture. The approach to the corpus constituted of Medieval ritualistic “songs” – or liturgical chant –, mobilizes the concepts of vocality, aural composition and performance, according to the anthropo-sociohistorical perspective – that is, which deals with the musical perception phenomenology, and with symbolic representations inherent in composition and performance artisanry. Thus, this study expounds a phenomenology of chanting act, of writing and reading music, putting forth questions about the meanings produced by the gathering of voice and chanted lyrics. Even in a notated music, “voice” is incorporated to scripture: in chant, the vocal sounds not only intone definite pitches, but recite speeches, producing verbal, discoursive senses. Then, after introductory discussions about Greek musical culture and its legacy in Christian music, this study focuses the former written sources of the Church cantus or plainchant, dated from 10th century on, thus, in the genesis of neumatic melodic notation. The nuclear question of the second part of this study is: how do poetic-religious voices materialize themselves in Christian monodic vocal composition? The researches of plainsong traditions of the studied period suggest that the cantus was, for a long time, an oral practice which developed mnemonic strategies: the neumes could be conceived as, primarily, signs to perform from memory. Thus, independently of whether neumatic notation meant or not an ideography of voice’s spatiality – along the historical trajectory of the semiotic development of musical notation –, neumes can be read as symbols for the movements of the voice, metamorphosed through memory by the act of manuscription. The emphasis of this study rests upon monodic vocal music chanted in Church rituals; the approach proposed here makes possible to inquire on melic, linguistic and poetic dimensions of vocality. Demonstrating the imbrications of voice and letter in vocal musical genders is to recognize that the rhythmic-melodic, prosodic and poetic resources, allied, orchestrate the production of musical meanings. This work finishes with considerations about voice performance as being an act of transmission and aural composition, conceiving performance and interpretation as recreation of repertories, and recomposition of musical memory.